Penegakan Hukum Terhadap Ketidaksesuaian Pemberian Upah Minimum Pekerja Di Era Globalisasi Ekonomi - Rahman, Irham; Suwadji; Fahamsyah, Ermanto; Kumala Sari, Nuzulia (Universitas Ekasakti, 2024)
The influence of economic globalization that is occurring in the current era has become a challenge for developing countries in the progress of national economic growth. To face these challenges, Indonesia made a legal breakthrough by enacting a law using the omnibus law method, namely Law Number 6 of 2023 concerning Job Creation (UU Job Creation). Apart from the polemic in the process of forming this law, the Job Creation Law issued a special Government Regulation relating to the latest minimum wage for workers. However, the legal issue still cannot be resolved because there are still workers who have not received the wages they should. The problem in this research is how to enforce the law regarding discrepancies in providing minimum wages for workers. The research method used in this research is normative research by examining related norms. And this research approach uses a statutory approach and a case approach. The results of this research are that law enforcement regarding non-compliance with the minimum wage for important workers is carried out by increasing inspections and supervision, namely by carrying out frequent inspections and supervision in workplaces. Administrative sanctions, legal demands. This can be done through courts or employment dispute resolution bodies, and campaigns and Advocacy, namely labor organizations publishing the names of violators as a more transparent form of law enforcement.